ORIGIN AND THEIR RELEVANCE LOFT IN THE MODERN CITY (Municipal economy of cities (Technical science), 2013)
The problems of a phenomena and concepts of "loft". The problems of conversion of industrial land and the use of lofts to meet the challenges of social housing.